Sunday

April 20, 2014

April 20, 2014

Posted by **David** on Sunday, September 16, 2012 at 6:57pm.

- Math -
**Reiny**, Sunday, September 16, 2012 at 8:35pma/(a+2)-1 = -(3a+2)/(a^2+4a+4)

a/(a+2)-1 = -(3a+2)/((a+2)(a+2))

multiply each term by (a+2)(a+2)

a(a+2) - (a+2)(a+2) = -3a-2

a^1 + 2a - a^2 - 4a - 4 = -3a-2

a = 2

**Related Questions**

algebra - 3(a+2)=4a I multiply 3*a+3*2=4a so 3a+6=4a I added 3a to 4a/ =7a and ...

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

math - what is the sum of 3a + b + a + b? 1)3a+2b 2)4a+2b 3)a3+b2 4)4a + b 5)6ab

algebra - want to know if this right simplify and show all work -3x^2+4xy+7y^2+2...

Algebra 2 - Solve. 4a-2≤a+1≤3a+4 4a-2-1≤a+1-1≤3a+4-1 4a-...

Math - 3a-2b=12 2a+b=1 multiply eq 2 x 2 4a+2b=2 eliminate b by subtracting eq (...

College Algebra - Solve each equation. If an equation has no solution, so ...

chemistry 2 - Which group from the periodic table contains two elements that ...

maths algebra - 3a-2(2a+4) 3a-2(2a + 4) you multiply the parenthesis by -2, ...

Math - In this problem: -2/a+2 + 3a/2a-1 First I made the denominators alike: -2...